Potential vs prevalent vs popular vs proven biodiesel feedstocks: A critical 4P selection process. (15th August 2021) - Anwar, Mohammad
Highlights: 4P (Potential, prevalent, popular and proven) biodiesel feedstocks are analysed. 18 technical, economic, environmental, and social criteria are used. 5 weighting methods, namely EQUAL, CRITIC, ENTROPY, AHP, and Fuzzy AHP used. 5 MCDA processes, namely PROMETHEE, WSM, WPM, and TOPSIS, and VIKOR are implemented. Soybean ranked as the worst feedstock and Coconut rated the best performer. Abstract: Due to severe geopolitical uncertainty, tensions between nations that produces fuel/oil, and trade sanctions, almost no nation can guarantee a consistent fuel supply and that can affect the progress or development of countries significantly as fuel is the backbone of the energy supply. Counties are exploring different alternative energy sources that can be sustainable and locally available. Waste-based biofuel, i.e., biodiesel, can be an excellent cheap alternative to diminish the fuel supply–demand conflict and can also play an important role in mitigating the adverse effects of greenhouse gas emissions in the environment. This study focuses on four biodiesel feedstocks that are classified as having the most potential (microalgae oil), being the most prevalent (palm oil), the most popular (soybean oil), and the most proven (coconut oil) identified by the current researchers. The Scopus research database recognises these biodiesel feedstocks. The ranking among these studied biodiesel feedstocks is focused on technical, economic, environmental, and social aspects with eighteen criteria. There are five weighting methods used in this study, namely EQUAL, Criteria importance through intercriteria correlation (CRITIC), ENTROPY, Analytical hierarchical process (AHP), and Fuzzy Analytical Hierarchical Process (FAHP). Five multiple criteria decision analysis processes, namely PROMETHEE, Weighted sum method (WSM), Weighted product method (WPM), Technique for order preference by similarity to ideal solution (TOPSIS), and VIse Kriterijumska Optimizacija Kompromisno Resenje (VIKOR) are applied for ranking these feedstocks. The results reveal that Coconut oil rated the best followed by Microalgae and Palm oil, whereas Soybean was considered to be the worst performer among those feedstocks. This ranking of biodiesel feedstocks is important for commercialisation purposes as well as providing a clear picture to the researchers, scientists, policymakers, and Government stakeholders.